Specifics of consumer behavior in modern Russia - O. B. Anikin; V. S. Makhonina (Вестник университета)
The article discusses the change in consumer behavior in the conditions of the epidemiological situation associated with the spread of the Covid-19 virus, as well as due to the aggravation of the international political situation caused by the start of a special military operation of the Russia in February 2022. These circumstances demonstrate the relevance of the study. The main purpose of the article is to identify the behavior features of the national consumer in the conditions of changing economic and foreign policy situation at the present stage. Particular attention is paid to the concept consideration of “consumer behavior” from the point of view of classical and neoclassical approaches. The article analyzes the behavior of consumers and examines the factors determining its change. The specifics of consumer behavior in the period from 2020 to 2023 are revealed. The importance of studying this topic at the present time is substantiated, as well as possible directions for changing consumer behavior and the work specifics of Russian companies in modern conditions are determined.